Effect of duration in the extraction of rendemen from mangga kuweni peel (Mangifera Odorata Griff) using MAE method - Abdurrahman Hanif; Asri Widyasanti; Selly Harnesa Putri (Universitas Darussalam Gontor, 2020)
Mango peel is one of the by-products that is wasted when processing the fruit into certain products. One form of mango peel utilization is by extracting the oleoresin content in it. Oleoresin is aextractive substance that contains the main components of flavoring in the form of volatile (essential oil) and non-volatile (resin and gum) substances,thesetwomaincomponentsplayanimportantroleindeterminingaromaandtaste.Thepurposeofthis study is to identify the best extraction treatment by MAE method of kuweni mango peel oleoresin, so that it can be an alternative form of storage for volatile compounds found in the skin of kuweni mango. This study used the microwave assisted extraction (MAE) method. Extraction was carried out using n-hexane solvent to extract the oleoresincomponent ofthemangoskinofthekuwenimango.Theratiooftheamount ofmaterial withthesolvent used is 1:10, with a raw material weight of 20 grams. The extracted solvent is evaporated using a rotaryvacuum evaporatortoproduceamoreconcentratedresult. MAEisdonefor1minute, 2minutes, 3minutes, 4minutesand 5 minutes. Microwave used 50% power. The parameters measured in this study were the yield of oleoresin extracted. The results showed that the yield of oleoresin from extraction was 42,25% for 1 minute, 44,55% for 2 minutes, 44.10% for 3 minutes, 22,80% for 4 minutes, and 22.35% for 5 minutes. The conclusion of this research is that the extract of mango kuweni peel oleoresin which is produced from MAE process with n-hexane solvent produces the best yield in the 2-minute extraction time treatment which is44.55%